Reforma del art. 1050 del Código Civil en relación a que se incluya como personas que no pueden ser testigos en un testamento solemne a los rufianes y meretrices - Hidalgo Costa, Sandra Elizabeth (2015)
Among the requirements to celebrate the marriage, Ecuadorian civil law requires certain formalities to be valid, which can cite the presence of competent witnesses, meaning suitable for people who are included within the disqualifications contemplated the same legal body, has to say about them that can not be witnesses under eighteen years. For the marriage may not witness the insane, deaf people, who can not make themselves understood verbally, in writing or by sign language, beggars, pimps and prostitutes convicted person who has deserved more four years in prison and those who do not understand the Castilian language or Quichua or Shuar or other ancestral language, if necessary. Likewise, the Civil Code, establishes the figure of solemn testament, that within the requirements the origin of two witnesses is established. But for the solemn act of the will, likewise determines who can not witness as the under eighteen; that may be found in interdiction, by reason of insanity; those now they find themselves deprived of reason; the blind; deaf people who can not make themselves understood verbally, in writing or by sign language; sentenced to any of the penalties designated in Article 311, paragraph 4º, the duration of the sentence; dependent notary who authorizes the will; foreigners not domiciled in Ecuador; and those who do not understand the language of the testator, subject to the provisions of Art. 1062. Unidentified excluding pimps and prostitutes. The will to be a ceremony and last will of the testator must be viewed in the Civil Code as a disabled person to witness the pimps and prostitutes because it affects the trustworthiness that should be saved as witnesses regarding the legality and transparency of the act probate